Determining brand strenghth against WOM with the mediation of customer satisfaction and business loyalty of Garuda Indonesia aircraft flight - Iriawan, Dean Pratiwi; Sumadi, Sumadi (Asian Management and Business Review, 2021)
The purpose of this research is to know and explain the effect of brand Strength on word of mouth, the effect of brand strength on customer satisfaction, the influence of brand strength on consumer loyalty, the effect of consumer satisfaction on word of mouth, the effect of consumer loyalty on word of mouth, the effect of consumer satisfaction on consumer loyalty. The population in this study were Garuda Indonesia consumers in Indonesia. The sample taken in this study were some of Garuda Indonesia consumers in Indonesia, amounting to 230 people. The data analysis in this study used the SEM method. The results of this study prove that brand strength has a positive effect on word of mouth, brand strength has a positive effect on customer satisfaction, brand strength has a positive effect on consumer loyalty, consumer satisfaction has a positive effect on word of mouth, consumer loyalty has a positive effect on word of mouth, satisfaction has a positive effect. towards consumer loyalty.